Phylogenetic analysis of six different species of Saraca L. (Fabaceae, Caesalpinioideae) based on chloroplast matK gene - SUJIT SIL; Kalyan De; ASOK GHOSH (Society for Indonesian Biodiversity, 2021)
Abstract. Sil S, De KK, Ghosh A. 2021. Phylogenetic analysis of six different species of Saraca L. (Fabaceae, Caesalpinioideae) based on chloroplast matK gene. Biodiversitas 22: 3880-3889. Saraca L. is one of the most important genera, with several horticultural and therapeutic values. Specific taxonomic and phylogenetic knowledge of Saraca through molecular data is essential for accessing its true medicinal benefits. Nineteen different Partial matK gene sequences of the chloroplast genome of six different species of Saraca, including four amplified and 15 retrieved from the NCBI gene bank, were place in a sequence alignment. The resulting data were examined to determine their phylogenetic and evolutionary interrelationships. The comparative analysis of different sequences of each of the species revealed intra-specific molecular diversity, and the comparison of the matK sequences of six different species defined their inter-specific molecular diversity. The analysis of partial matK sequences revealed the presence of 87 variable sites, 14 parsimony informative sites, 54 singleton sites, and 237 quadri-fold degenerate sites. The approximate nucleotide composition was A-31.02%, T-37.46%, C-16.06%, and G-15.46%. The value of transition/transversion bias was 0.90. About 522 codons were analyzed and the presence of 34 variable sites, 8 parsimony informative sites, and 25 singleton sites was observed within their respective amino acid sequences. The average pair-wise distance was 0.0444, and 189 segregating sites and 0.018809 nucleotide diversity were observed. The evolution of different species of Saraca and their phylogenetic interrelationships were observed by analyzing their matK sequences. The relative homogeneity of S. indica is quite low. S. dives had the earliest evolutionary trends while S. declinata had the most recent. S. asoca and S. indica are quite similar on the molecular level but can be treated as different species while the difference between S. declinata and one of its synonyms, S. palembanica, indicates the possibility of separating them into different species.